THE EFFICACY OF CORTICOSTEROID AFTER FACIAL NERVE NEURORRHAPHY: A SYSTEMATIC REVIEW - Monica, Desnita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: In case of comple transection of facial nerve, it is unclear whether or not corticosteroids will be beneficial after facial nerve neurorrhaphy.Aim: The purpose of this systematic review was to determine whether or not corticosteroids are effective in promoting facial nerve regeneration and functional recovery following complete transection and neurorrhaphy.Methods: Randomized controlled trials on human and animal models from Ovid MEDLINE and Ovid EMBASE that studied the efficacy of corticosteroids in total facial nerve damage followed by neurorrhaphy. Electrophysiology, histology, and functional recovery were the methods that were used to evaluate the results. On the other hand, there was no randomised controlled experiment carried out on humans. In a clinical context, it's possible that it won't be possible to conduct human trials that involve histology.Results: Six animal investigations with a total of 248 participants met the inclusion criteria. Electrophysiological results revealed no differences between systemic corticosteroids and controls in terms of latency and amplitude. The results of a comparison between topical corticosteroid and the control group revealed no differences in latency and amplitude. In histologic outcomes, there were no differences in axon diameter between the systemic corticosteroid and control groups; however, the control group had thicker myelin. Comparing systemic corticosteroid to a placebo in terms of eye blinking, the results favoured the placebo.Conclusion: When analysing electrophysiologic and functional recovery outcomes in animal models, this study did not demonstrate any possible benefits of systemic or topical corticosteroid administrations after facial nerve neurorrhaphy in complete transection.